Bathing suit ichthyosis. - Bonifazi, E. (European Journal of Pediatric Dermatology, 2009)
A fifteen months baby girl came to our observation due to diffuse scaling prevailing on the trunk. First born from non consanguineous parents, she was born full term with a weight of 3.1 kg and a height of 50 cm. There were no pathological events during the pregnancy and the perinatal period. Her mother did not see skin abnormalities at birth. However, from the second month she noted lamellar scaling not preceded by clinically evident inflammation and prevailing on the trunk. The physical examination put in evidence lamellar scaling affecting the trunk and the root of the upper limbs, stopping distinctly (Fig. 1) on the limit between the upper third and the lower two-thirds, almost to outline the shape of a T-shirt. The clinical features and the distribution of the lesions led to the final diagnosis of bathing suit ichthyosis.